Educational Innovation for Sustainable Development : Report of the Third UNESCO-ACEID International Conference (Bangkok, Thailand, December 1-4, 1997). (UNESCO Principal Regional Office for Asia and the Pacific, 2020)
Conference on Educational Innovation for Sustainable Development are indeed vital ones for all educators, whether they be in government departments, schools, teacher training colleges, universities or NGOs.